(untitled) (International Journal of Built Environment and Sustainability, 2022)
The Covid-19 pandemic becomes a primary issue in urban development that requires several supporting facilities and infrastructures to handle. The adequate water supply to ensure the washing hand and bathing as part of health protocol implementation is crucial for drought-prone areas. Meanwhile, the government strategies on drought handling by assisting the water trucks are considered a temporary solution. Hence, this study examines urban design initiatives to deal with Covid-19 impact on the water sector, particularly in Semarang drought-prone areas. The research used a quantitative method by overlaying physical variables such as the soil type, slope, and water supply coverage to determine the drought level map. Afterward, the drought level compared with the population growth and community’s economic capacity to describe the area’s vulnerability. Besides, the existing drought handling strategies were analyzed to examine the impact. This study utilized secondary data such as the government institution websites as well as Google maps. The analysis results point out that most of drought-prone areas did not serve by government water service and relied on the community-based water supply system. In addition, 25% of the inhabitants are categorized as a low-income community, so that they prefer to take water from the river or spring than have to expend more to buy the water. Meanwhile, the existing initiatives on drought handling did not have significant impacts because of a lack of knowledge and unclear regulation. The Water Sensitive Urban Design (WSUD) concept has already been adopted, yet the implementation was still small-scale and unsustained. Therefore, it is necessary to consider the physical, socio-economic, and political aspects in implementing the drought handling initiatives.